(untitled) (Research, Society and Development, 2021)
Introduction: The demand for restorative dental treatments has been growing over the last few years. Changes in the color of anterior teeth have a greater aesthetic impact, due to their greater visibility when smiling and communicating. Objective: to review the literature on the approach of restorative techniques for direct restorations in darkened teeth. Methodology: a bibliographic review was carried out in the Pubmed, Scielo, BBO and LILACS databases. Articles, publications and research published in the period from 2015 to 2021 that were related to the subject of this study were selected. Results: the great challenge in making direct veneers on darkened teeth is the masking of the altered substrate. To minimize this unwanted effect, the professional can increase dental wear, or in a more conservative way, use opacifiers, defined as resins capable of preventing the passage of light and masking unwanted colors from the dental substrate. Conclusion: the correct diagnosis of tooth darkening, in addition to mastering the manipulation and adequate knowledge of opacifying agents are essential to obtain a natural smile esthetics and success in the treatment with direct veneers of anterior teeth. The use of opacifying resins is an adjunct in the direct veneer technique for darkened teeth and seems to bring satisfactory results.